LA VISION HOLISTE DE LA FORET, FONDEMENT DES DROITS FONCIERS DES PEUPLES AUTOCHTONES - Marie BOUNDAWANE (IJRDO - Journal of Social Science and Humanities Research, 2019)
The emergency for the RDC to start the question of clarification of the fundamental rights of the autochthonous peoples quickly to allow those - here to regain their dignity and to benefit from all advantages bound to the forest and touts the services that she/it offers is today a firm engagement. The clarification of the fundamental rights of the autochthonous peoples is a challenge of bottom and shape to allow them to benefit from all dividends of the mechanisms innovative of financing bound at the forests. To refuse to raise this challenge, the screams of alarm will continue to be thrown against the violations of the common laws and traditional of the autochthonous peoples in order to protect their existence and self-determination.